2022
DOI: 10.2106/jbjs.21.00982
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes After Anatomic and Reverse Shoulder Arthroplasty for the Treatment of Glenohumeral Osteoarthritis

Abstract: Background: Reverse shoulder arthroplasty (RSA) is increasingly being utilized for the treatment of primary osteoarthritis. However, limited data are available regarding the outcomes of RSA as compared with anatomic total shoulder arthroplasty (TSA) in the setting of osteoarthritis. Methods:We performed a retrospective matched-cohort study of patients who had undergone TSA and RSA for the treatment of primary osteoarthritis and who had a minimum of 2 years of follow-up. Patients were propensity scorematched by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(7 citation statements)
references
References 27 publications
0
6
0
1
Order By: Relevance
“…23,24 The majority of papers in the current literature show that there is no difference in overall complication rate between aTSA and rTSA, although the nature of the complication is different. 15,[25][26][27] However, other studies demonstrate that rTSA has a higher complication rate compared to aTSA, as it can increase mechanical complications, blood loss, postoperative pain, and the length of stay. The most common complication found in our study following aTSA is rotator cuff tear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23,24 The majority of papers in the current literature show that there is no difference in overall complication rate between aTSA and rTSA, although the nature of the complication is different. 15,[25][26][27] However, other studies demonstrate that rTSA has a higher complication rate compared to aTSA, as it can increase mechanical complications, blood loss, postoperative pain, and the length of stay. The most common complication found in our study following aTSA is rotator cuff tear.…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 29 Additionally, other studies report no difference in the functional outcome between aTSA and rTSA. 1 , 11 , 25 , 26 Mowbray et al 18 included 2490 patients for their functional outcomes (OSS), where they reported that for elderly population aged over 70 with osteoarthritis as primary diagnosis and intact rotator cuff, aTSA was associated with an improved OSS compared to primary rTSA. 18 We were unable to include this clinical outcome in our meta-analysis as Mowbray et al 18 was the only study using OSS.…”
Section: Discussionmentioning
confidence: 99%
“…Neben dem beachtlichen Fortschritt im Bereich der inversen Schulterendoprothetik verbleiben weiterhin beachtliche Einschränkungen und Komplikationsmöglichkeiten. ▪ So zeigen sich trotz optimierter biomechanischer Aspekte, variabler Implantatkonfigurationen und einem allgemein erhöhten Erfahrungsschatz im Bereich der inversen Endoprothetik Bewegungseinschränkungen im Vergleich zur anatomischen Situation, die insbesondere im Bereich des rotationsbasierten Bewegungsausmaßes hervorstechen [67]. ▪ Des Weiteren konnten Probleme, etwa das skapuläre Notching, zwar reduziert, bislang aber nicht eliminiert werden, sodass vergleichende Arbeiten weiterhin Notching-Raten von bis zu 14,8 % beschreiben [68].…”
Section: Limitationen Der Inversen Schulterendoprothetikunclassified
“…However, there has been a limited amount of current literature comparing RSA and TSA in the setting of osteoarthritis. Kirsch et al 8 conducted a retrospective propensity-score-matched cohort analysis to compare clinical outcomes between RSA and TSA in 134 patients with primary osteoarthritis. At a mean follow-up of 30 months, no significant differences were observed in patient-reported outcome measures (PROMs) (i.e., ASES, SANE, and VAS pain scores) between RSA and TSA.…”
Section: Reverse Shoulder Arthroplastymentioning
confidence: 99%